THEORETICAL AND METHODOLOGICAL BASIS OF DEVELOPING ANALYTICAL AND MATHEMATICAL THINKING ON THE BASE OF A DIALECTIC APPROACH IN EDUCATION - Fazliddin Batirovich Kurbanov (Web of Journals Publishing, 2024)
The article analyzes the pedagogical necessity of developing analytical thinking based on a dialectical approach in educational institutions, the current state of developing thinking in today's higher education institutions, and the possibilities and solutions for eliminating shortcomings. The article also discusses the theoretical and methodological aspects of pedagogical practice aimed at developing analytical thinking.
Keywords: Education and training, innovation, technology, methodological requirements, thinking, debate, analytics.